Genomic data from Chinstrap penguin ( Pygoscelis antarctica ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The Chinstrap penguin inhabits a variety of islands and shores in the Southern Pacific and the Antarctic Oceans. It has a narrow black band under its head. They breed in Antarctica, Argentina, Bouvet Island, Chile, the Falkland Islands, the French Southern Territories, and South Georgia and the South Sandwich Islands. Populations of Chinstrap penguin are considered to be decreasing overall, however in many sites the populations are increasing or stable. They are considered as Least Concern by the International Union for Conservation of Nature (IUCN). We sequenced the genome of an adult Chinstrap penguin from Thule Island, South Sandwich Islands (provided by Tom Hart) to a depth of approximately 125x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled scaffolds of high quality sequences total 1.24Gb, with the contig and scaffold N50 values of 115.56Kb and 5.89Mb respectively. We identified 15488 protein-coding genes. ...